Nonresponse Error in Mail Surveys: Top Ten Problems - Jeanette M. Daly; Julie K. Jones; Patricia L. Gereau; Barcey T. Levy (Nursing Research and Practice)
Conducting mail surveys can result in nonresponse error, which occurs when the potential participant is unwilling to participate or impossible to contact. Nonresponse can result in a reduction in precision of the study and may bias results. The purpose of this paper is to describe and make readers aware of a top ten list of mailed survey problems affecting the response rate encountered over time with different research projects, while utilizing the Dillman Total Design Method. Ten nonresponse error problems were identified, such as inserter machine gets sequence out of order, capitalization in databases, and mailing discarded by postal service. These ten mishaps can potentiate nonresponse errors, but there are ways to minimize their frequency. Suggestions offered stem from our own experiences during research projects. Our goal is to increase researchers' knowledge of nonresponse error problems and to offer solutions which can decrease nonresponse error in future projects.